Fee or Free: When Should Firms Charge for Online Content? - Lambrecht, Anja; Misra, Kanishka (Management Science, 2017)
Many online content providers aim to compensate for a loss in advertising revenues by charging consumers for access to content. However, such a choice is not straightforward because subscription fees typically deter customers, and a resulting decline in viewership further reduces advertising revenues. This research examines whether firms that offer both free and paid content can benefit from adjusting the amount of content offered for free. We find that firms should offer more free—and not paid—content in periods of high demand. We motivate theoretically that this policy, which we term “countercyclical offering,” may be optimal for firms when consumers are heterogeneous in their valuation of online content and this heterogeneity varies over time. Using unique data from an online content provider, we then provide empirical evidence that firms indeed engage in countercyclical offering and increase the share of free content in periods of high demand. This paper was accepted by Matthew Shum, marketing.